Thinking about Change: American Theorizing and Chinese Reasoning on World Politics. Issue 2 (10th May 2018) - He, Kai; Chan, Steve
Abstract: This essay addresses conceptions of change in two influential U.S. theories of international relations (power-transition theory and leadership long-cycle theory), and their resonance with Chinese predilections in thinking about and coping with change. We examine both convergences and distinctions between American IR theorizing and Chinese understanding on three key questions concerning change in world politics: (1) who is the key agent of change? (2) why does change take place? And (3) how does change happen in history? We highlight the bimodal feature of Chinese strategic thinking of how to make a change in world politics. We suggest that Chinese leaders respond to pressures stemming from both their domestic and international environment. They tend to be more risk-acceptant when facing a deteriorating situation and more inclined to pursue a moderate approach when facing a benign environment. External actors, especially the United States, will play an important role in shaping China's choices.